(untitled) (International Journal of Engineering and Computer Science, 2015)
The paper puts on the basis of idea which focuses on cost reduction and enhancing the quality of service in the field of digital advertising technologies. This work is about a remotely managed smart advertising system designed using Raspberry pi along with python programming. The digital advertising display system designed is based on various methods of using LCD screen, as well as other display devices. This system is very efficient to provide advertising information, to those people who live in public areas but; some areas that does not convenient to build- up the other types of advertise hoarding boards for their information. The Raspberry Pi model and its web interface using Wi-Fi dongle. This proposed system aims to substitute another system interface with Raspberry Pi, which will not only drastically reduces the cost involved but also will help achieving quality of services as the system will consume a smaller amount of power and become the system smartness. In this digital advertising system using Raspberry Pi B+ model. The multiple display screens are placed at such place having maximum people crowded areas and those areas are mostly attractive in city. The contents on the screen are made up of several images files which are continuously running having different contents. The main goal of this project is broadcasting information and remotely controls it. The broadcasting information such as, buses and bus station, train and train station, shopping malls, city square, road highways, subways, hospital, in conference hall. It is also used in educational institutes like colleges and schools for the purpose of displaying notices for students and also displaying all institutional growth and achievements information for visitors. Similarly this application for industry purpose of displaying notices, information about current technologies and market scenario; which is useful for all company’s employee.